Criteria of Categorizing Logistics and Distribution Centres - Darko Babić; Anđelko Šćukanec; Kristijan Rogic (Promet - Traffic&Transportation, 2012)
Logistics and distribution centres represent very significant infrastructure elements of the macro-logistic system. The creation of the logistics and distribution centres and their connection into a wide (global) network have resulted in the creation of conditions for an adequate distribution of labour and significant increase in the productivity of all the logistics elements and processes, noting that the logistics and distribution centres in this concept have a superregional significance.This paper represents the summary (results) of the research that was carried out on a large number of logistics and distribution centres with the aim of considering the complexity and the issues related to the logistics and distribution centres and the distribution network, their elements and action of the subsystems according to the following criteria: spatial, technical, technological, and organizational, with the aim of defining the categorisation model of the logistics and distribution centres.The analysis of the selected data collected during the research has resulted in defining of the categorisation model of the logistics and distribution centres which foresees six categories. Each of the foreseen categories has been defined according to the set model by the mentioned traffic, technical and technological, and organisational characteristics and the level of service. This is precisely where the application of the categorisation model of the logistics and distribution centres can be found, which will define the relevant categories of the centres applicable in the creation of effective distribution